Morphology and multigene phylogeny reveal a novel Stagonospora species (Massarinaceae, Dothideomycetes) from Thailand - Bhagya, Amuhenage T.; Phukhamsakda, Chayanard; Tanaka, Kazuaki; Jones, E.b. Gareth (Phytotaxa, 2024)
Stagonospora is an asexual morph genus that is classified under Massarinaceae in Dothideomycetes. Stagonospora species have been recorded in both tropical and temperate regions. Several species have been reported as saprobic or opportunistic pathogenic lifestyles on grasses and grass-like plants. In this study, Stagonospora was collected from a Typha species in Sam Roi Yot wetland in central Thailand. Morphological examination was coupled with multi-loci phylogenetic analyses using maximum likelihood and Bayesian interference of a data set containing large subunit ribosomal rDNA (LSU rDNA), internal transcribed spacer (ITS) regions, small subunit ribosomal rDNA (SSU rDNA), and translation elongation factor 1-alpha (tef1-α) sequences. Our new taxon is distinguishable from other Stagonospora species by having hyaline, one-septate conidia that taper toward the base. This discovery holds significant value in comprehending the fungal diversity within Thailand’s wetlands and the specific fungal communities linked to Typha plants.